The role of kindergarten institutions in providing children with the concept of traffic safety "A field study from the point of view of kindergarten teachers in Lattakia" (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The study aimed to identify the role of kindergarten institutions in providing children with the concept of traffic safety. The study sample consisted of 104 private kindergarten teachers in the city of Lattakia. Items, the study used the descriptive approach, the role of kindergartens as a whole came in a medium degree in providing children with the concept of traffic safety, while the teachers played a high degree in providing the child with the concept. It was found that there are no differences according to the experience variable, while there are differences in favor of educational qualification diploma holders.The study concluded by presenting a set of proposals, including holding seminars and dialogues between the kindergarten administration and teachers on the one hand, and parents and their children, and the traffic department on the other hand, activating the educational pillars, especially related to the concept of traffic safety. Key words: traffic Safety, Kindergarten teachers, Kindergarten institutions